ANALISIS KINERJA DPRD DALAM PENYUSUNAN PERATURAN DAERAH KOTA PALU - Ishak, Widharto (Katalogis, 2016)
This study aims to determine the performance of Palu City’s House of Representatives (DPRD Kota Palu) in legislative drafting. The research method of this study was qualitative research by selecting informants who can provide data in accordance with the needs of this of this study with purposive method. Data collection techniques in this study were: observations, interviews and documentations. Based on the results of the analysis of DPRD Kota Palu in legislative drafting, it can be concluded that it has not gone well, because only one of the 5 aspects used as analyzing tools in this study which went well, that is Responsbillity. The 4 other aspects that have not gone well were Productivity, Quality of Services, Responsivness and Accountability.